Where Goes the Neighbourhood? Refugee Resettlement and Urban Development in a Disempowered City - Moslow, Chiara (eCahiers de l'Institut, 2023)
This paper explores the intersection of urban restructuring and refugee resettlement. Centring around a case study of Buffalo, New York (NY), USA, it adds to the small but growing number of studies on resettlement in post-industrial contexts. Buffalo is experiencing economic and population growth, termed by some as the city's renaissance (even the refugee renaissance), while others regard it as gentrification and exclusionary development. At the same time, the city has become one of the largest resettlement sites in the country. In politicians' statements and the media, refugees are credited with being one of the key drivers for this development in the city. Through interviews with various stakeholders, I explore how these phenomena are understood. I argue that this convening of factors creates a particular conception of the figure of the resettled refugee. In Buffalo, refugees emerge as a particularly valued form of other, capable of driving development in a way that fits ideally within the narrative of 'rust to reinvention'. As such, they become outside economic development agents, divorced from the challenges faced by struggling residents for decades. Resettlement actors navigate this conversation, recognising the challenges faced by refugees and other residents, while at the same time carrying forward prevailing narratives and frames. We extend our heartfelt thanks to the Vahabzadeh Foundation for financially supporting the publication of best works by young researchers of the Graduate Institute, giving a priority to those who have been awarded academic prizes for their master's dissertations.